The Megaphone as Material Culture:: Design, Use and Symbolism in North American Society, 1878-1980 - Edwards, Bret (Material Culture Review)

(untitled) (National Museums of Canada, 2011)
Abstract This article examines the ways in which the megaphone was utilized as an object of communication and as a semiotic cultural symbol in North America between the late 19th and late 20th century. Through this analysis, it argues that a correlation can be established between technological modifications to the megaphone and pronounced changes in its users, use and cultural meaning over time. Equipped with limited communicative capabilities, the original, vintage megaphone occupied a prominent role in the patriarchal power structure and culture of leisure of the Victorian era as a gendered and exclusive instrument that accorded knowledge and stature to its primarily male users. This association with power and privilege, however, grew more tenuous by the early-post-war era. In response to dramatic advances in design and technology and in conjunction with growing societal polarization, the modern successor to the original megaphone became ascribed with new cultural meanings antithetical to the Victorian era, and evolved into a polarizing cultural symbol as a politicized and democratized object utilized by a diverse set of social actors to both enforce and contest the status quo.